NUEVO REGISTRO DE UNA POBLACION DE FITZROYA CUPRESSOIDES (MOLINA) I.M.JOHNST. EN SU LIMITE NORTE EN LA ISLA DEL REY, CHILE - Soto, Daniel P. (Gayana Botánica, 2009)
This short communication describes a small undocumented population of Fitzroya cupressoides (Molina) I.M.Johnst. in the northern limit of the Chilean Coastal Range. The stand is of 1.19 ha in size in 39º53’S, 73º19’O at 25 m a.s.l. This small isolated stand is inserted in a highly fragmented landscape dominated by exotic tree plantations. This unique condition makes urgent the development of a genetic and biogeographical conservation strategy.